BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
A.P. Misra 78th Birthyday Felicitation Volume). Cereals, Pulses, Oil Seeds, and cash Crops. Editors V.P. Agnihotri, Om Prakash, Ram Kishun, and A.K. Misra. International Books & Periodicals Supply Service, 38 Nishant Kunj, Pitampura, Delhi 110 034. 1996. 274 pp. Price Rs. 750/-. Chytrids of India - By R. Dayal, M.D. Publications Pvt. Ltd., New Delhi. 110002.316 pp. Price Rs.700.00 Guava Diseases (An annotated bibliography 1907-1990). By A.K. Misra and Om Prakash. Publishers: Bishen Singh Mahendra Pal Singh, Dehradun. 1994. pp. 132. Price Rs. 250/-